2014
DOI: 10.1021/jp503367v
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Embedded Two-Dimensional C3N4–Graphene Nanocomposite: A Multifunctional Material

Abstract: The lack of intrinsic spin polarization in graphene as well as in its several composites limits their usage as suitable spintronic material. Using long-range dispersion corrected density functional theory, we explore the structural, electronic, magnetic, and optical properties of recently synthesized [Liu, Q.; Zhang, J. Langmuir 2013, 29, 3821−3828] two-dimensional graphitic carbon nitride (g-C 3 N 4 ) stacked graphene (C 3 N 4 @graphene) where 3d transition metals (TMs) are embedded in the cavity of g-C 3 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 55 publications
1
61
0
Order By: Relevance
“…These porous membranes can act as natural molecular sieves, and have great potential for future industrial applications, such as hydrogen [33][34][35][36][37][38][39][40], isotope [41][42][43][44], and other gas separation and purification [45]. Among these porous structures, g-C 3 N 4 has attracted considerable attention owing to its potential applications in solar energy conversion [46][47][48], spintronics devices [49,50], energy storage [51] etc. The framework of g-C 3 N 4 consisting of tri-s-triazine (heptazine) rings was demonstrated to be the most stable allotrope among various 2D carbon nitrides under ambient conditions [52].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These porous membranes can act as natural molecular sieves, and have great potential for future industrial applications, such as hydrogen [33][34][35][36][37][38][39][40], isotope [41][42][43][44], and other gas separation and purification [45]. Among these porous structures, g-C 3 N 4 has attracted considerable attention owing to its potential applications in solar energy conversion [46][47][48], spintronics devices [49,50], energy storage [51] etc. The framework of g-C 3 N 4 consisting of tri-s-triazine (heptazine) rings was demonstrated to be the most stable allotrope among various 2D carbon nitrides under ambient conditions [52].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[11][12][13] Theoretically, carbon nitride naturally exists in different phases, [14,15] it was believed that the graphitic structures are the most stable under ambient conditions. [28][29][30] The 5d transition metal-doped tri-s-triazine-based g-C 3 N 4 shows magnetic anisotropy, [29] and -2 -the 3d transition metal-doped cases demonstrated variously structural, electronic, magnetic, and optical properties. Experimental and theoretical studies have confirmed that the coplanar tri-s-triazine based g-C 3 N 4 is more stable than triazine-based one by about 30 KJ mol -1 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] In analogy to graphene and BN, graphitic-C 3 N 4 (g-C 3 N 4 ) is of interest due to its promising potential applications in the field of photocatalysis. [23][24][25][26][27][28][29][30][31][32] To improve their performances, generally, chemical doping is an effective strategy to modify the electronic structures and magnetic properties. The widely studied g-C 3 N 4 structure has two phases: the triazine-based structure and the tri-s-triazine-based structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] These units are linked together by sp 2 -hybridized nitrogen (or carbon) atoms, which lead to a chemical formula of C 3 N 4 (or C 4 N 3 ), 13,14 or directly joint together via C-C covalent bonds with a chemical formula of C 6 N 6 . Theoretical studies have showed that these graphitic carbon nitride materials exhibit exotic properties such as electron spin-polarization, 16,17 half-metallicity, 18,19 spin-gapless semiconduction, 20,21 and topological nontriviality. Theoretical studies have showed that these graphitic carbon nitride materials exhibit exotic properties such as electron spin-polarization, 16,17 half-metallicity, 18,19 spin-gapless semiconduction, 20,21 and topological nontriviality.…”
Section: Introductionmentioning
confidence: 99%